Pemetaan Tujuan Kaskade COBIT 5 Pada Pengelolaan Layanan Teknologi Informasi di Instansi Pemerintah - Nugraha, Gamal Febri; Selo, S; Nugroho, Eko (ReTII, 2017)
Management of IT services (IT) is important so that the implementation of the business process can proceed smoothly. The management of IT services performed by the Bagian SIP at Inspectorate Generale Ministry of Finance (MoFIG) still has a lot of problems cause by shortage of IT governance at management of IT service. This research will be mapping COBIT cascade goals on management of IT service aspects. It using COBIT framework 5. The first step is the initial phase of the study of literature, the formulation of the background purpose and benefits of the research. The next step is the problem solving phase. It consists of mapping enterprise goals, mapping IT-related goals, and mapping of IT-related goals with the COBIT 5 processes. It produces seven (7) processes in COBIT. Keywords : COBIT, COBIT Cascade goals, enterprise goals, IT-related goals, IT services